2018
DOI: 10.1371/journal.pone.0207088
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of incidental parathyroidectomy in thyroidectomy: A systematic review and meta-analysis

Abstract: IntroductionPostoperative hypocalcemia is the most common complication of thyroidectomy. Incidental parathyroidectomy (IP) was thought to be associated with postoperative hypocalcemia. However, according to previous studies, the risk factors and clinical outcomes of IP remain controversial.MethodsEligible studies were searched in databases including PubMed, Web of Science, and EMBASE from January 1990 to September 2017. Articles focusing on the relationship between IP and postoperative hypocalcemia were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 57 publications
(55 reference statements)
4
50
1
1
Order By: Relevance
“…Thus the routine use of calcium and vitamin D in early post-operatory period of time is recommended. This combination is useful for both transitory and permanent hypothyroidism (34).…”
Section: General Datamentioning
confidence: 99%
“…Thus the routine use of calcium and vitamin D in early post-operatory period of time is recommended. This combination is useful for both transitory and permanent hypothyroidism (34).…”
Section: General Datamentioning
confidence: 99%
“…Thyroidectomy is a common, relatively safe surgical procedure, which is associated with <5% morbidity rate [1]. The main postoperative complications of thyroidectomy include injury to the parathyroid glands and recurrent laryngeal nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its small size and close proximity to the thyroid tissue, inadvertent injury to the parathyroid glands by devascularization and accidental resection are inevitable, which most often can result in symptomatic hypoparathyroidism and hypocalcemia [2,3]. Hypocalcemia could either be transient or 1 2 3 4 5 6 1 permanent. While the reported incidence of the transient hypocalcemia ranges between 10% and 46%, the permanent one ranges between 1.5% and 4% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Low PTH levels at postoperative period are known to be a risk factor for developing hypocalcemia. HPP may develop as a result of dissection of parathyroid glands, malignancy, ligation of the thyroidal arteries remote from the thyroid gland, or inadvertent excision of the parathyroid glands [11,12]. Our study demonstrated a link between inadvertent parathyroid gland excision and developing hypocalcemia.…”
Section: Discussionmentioning
confidence: 54%